(untitled) (Diametros, 2025)
Giubilini, Gur-Arie, and Jamrozik (2025) argue that the non-expert public’s appraisal of someone as an expert is necessary for whether they have expert authority. According to them, expertise is contingent on whether someone possesses some “set of epistemic features that warrant trusting” them “as an expert.” Whether someone has these features depends on whether the public believes that person is reliable. This is partly because the public is vested in domains that affect their interests and, therefore, whether putative experts satisfy their responsibility to fulfill those interests. Here, I offer three objections to their argument, addressing their concerns with objective accounts of expert authority, the lay public’s ability to evaluate expert claims, and the adequacy of transparency for facilitating trust. I close by acknowledging the difficult epistemic position of non-experts but point toward accounts that address the authors’ concerns while nonetheless preserving the objectivity of expert authority.